PROSES PEMBUATAN SELONGSONG TABUNG PELINDUNG DETEKTOR GEIGER MULLER TIPE SIDE WINDOW - Gunarwan Prayitnyo (Jurnal Perangkat Nuklir, 2007)
A fabrication of Geiger Muller detectors tube has been made in BA TAN electronics laboratory Yogyakarta. The tube is made by aluminium solid material. The aluminium solid was lathed by lathe machine, to become like tube. In other side which was processed by the same manner, to be the tube cup. The function of the tube is to protect the detector from any hard substances, so that it will not break. The fabrication of the detectors tube is the finishing tough  and finishing work and the final step for detector tube fabrication type side windows. Pembuatan selongsong tabung detector Geiger muller tipe side window pernah dibuat di BATAN Yogyakarta. Tabung terbuat dari bahan aluminium solid atau padat. Batangan aluminium tersebut dibubut hingga menyerupai tabung. Pada bagian lain diproses dengan cara yang sama dan berfungsi sebagai tutup,. Tempat tabung detector berfungsi sebagai pelindung tabung dari benturan benda keras, sehingga tidak pecah. Pembuatan selongsong tabung ini sebagai penyempurnaan dan penyelasaian tahap akhir untuki pembuatan detector Geiger Muller tipe side window.